Direct thrombin inhibitors: novel antithrombotics on the horizon in the thromboprophylactic management of atrial fibrillation. Issue 956 (3rd June 2005) - Katira, R; Chauhan, A; More, R S
Abstract : Antithrombotic agents have verified efficacy in reducing the thromboembolic risk associated with atrial fibrillation. This article focuses on the emergence of a new oral direct thrombin inhibitor, ximelagatran, into the arena of atrial fibrillation thromboprophylaxis. This review does not cover atrial fibrillation in the context of valvular heart disease. The efficacy of aspirin and warfarin will be discussed briefly.